Complement receptor 1 gene (CR1) intragenic duplication and risk of Alzheimer’s disease - Kucukkilic, Ezgi; Brookes, Keeley; Barber, Imelda; Guetta-Baranes, Tamar; Morgan, Kevin; Hollox, Edward (Springer, 2018)
Single nucleotide variants (SNVs) within and surrounding the complement receptor 1 (CR1) gene show some of the strongest genome-wide association signals with late-onset Alzheimer’s disease. Some studies have suggested that this association signal is due to a duplication allele (CR1-B) of a low copy repeat (LCR) within the CR1 gene, which increases the number of complement C3b/C4b-binding sites in the mature receptor. In this study, we develop a triplex paralogue ratio test (PRT) assay for CR1 LCR copy number allowing large numbers of samples to be typed with a limited amount of DNA. We also develop a CR1-B allele-specific PCR based on the junction generated by an historical non-allelic homologous recombination event between CR1 LCRs. We use these methods to genotype CR1 and measure CR1-B allele frequency in both late-onset and early-onset cases and unaffected controls from the United Kingdom. Our data support an association of late-onset Alzheimer’s disease with the CR1-B allele, and confirm that this allele occurs most frequently on the risk haplotype defined by SNV alleles. Furthermore, regression models incorporating CR1-B genotype provide a bitter fit to our data compared to incorporating the SNP-defined risk haplotype, supporting the CR1-B allele as the variant underlying the increased risk of late-onset Alzheimer’s disease.